CFD Simulation of Air Cyclone Separator - Nuha wathq Nema; Saad Nahi Saleh; Fayadh Mohamed Abed (Tikrit Journal of Engineering Sciences, 2016)
A computational fluid dynamics model was developed for air cyclone separator in order to predict the flow pattern inside the cyclone using an Eulerian approach, three dimensions Reynolds-Average Navier-Stokes equations, closed via the Reynolds Stress model as a turbulence model for air flow. The particles were modeled as a discrete phase model using the Lagrangian transport model with turbulent particle dispersion. Computational fluid dynamics modeling was employed to investigate fluid flow patterns and particle trajectories at steady state operating conditions of Stairmand cyclone. Analysis of a computational fluid dynamics simulation accurately revealed that the air flow behavior in cyclone separator consists of two vortexes : an outer vortex with a downwardly directed axial flow and an inner vortex with an upwardly directed flow, this flow profile known as Rankine vortex. A low-pressure zone appeared in the center line of the cyclone due to high swirling velocity. The results showed that the pressure drop increased with increasing the inlet air velocity. The results of the collection efficiency showed that the efficiency increased as the particles diameter increased. A good agreement achieved between the simulation results and published experimental results. The computational fluid dynamics code (ANSYS FLUENT 14.5) with the Reynolds Stress model as the turbulence model, predicted very well the flow field parameters of cyclones and can be used in cyclone design for any dimensions.